ANALISA KADAR KARBOKSIHEMOGLOBIN (HbCO) PADA DRIVER OJEK ONLINE (GO-JEK) DAN PETUGAS SUKARELAWAN PENGATUR LALULINTAS DI SURAKARTA - Indah Tri Susilowati; Litta Adinar Widihastuti; Elma Risma Juniawati (Jurnal Kesehatan Kusuma Husada, 2021)
Carbon monoxide (CO) gas is a colorless, odorless, tasteless, non-irritating, flammable and highly toxic gas, and does not dissolve in water. Carbon monoxide is exposed to the body, binds to hemoglobin and inhibits oxygen to form carboxyhemoglobin. This study aims to determine carboxyhemoglobin levels in online motorcycle drivers (GO-JEK) and traffic control volunteer officer in Surakarta in Surakarta with the conway diffusion cell method. This research is a descriptive study with a quota sampling technique and the analysis used is a simple linear regression test. The subjects of this study were 12 respondents drawn from the population in accordance with specified criteria. Examination of COHb levels in the conway diffusion cell method uses a UV-VIS spectrophotometer. The results showed that description of HbCO levels for the 12 samples of GO-JEK drivers and SUPELTAS <3.5% which showed that they were still above normal, the systolic blood pressure description in the normal category was 75%, while the abnormal category was 25% and for diastolic blood pressure included the normal category was 58% while the abnormal one was 42%. Keywords: HbCO, conway diffusion cell method, online motorcycle taxi driver (GO-JEK), traffic control volunteer officer.